The evidence for plastic surgery - Stone, Christopher (Christopher A.) (Tfm Pub., 2008)
In this book the diverse spectrum of of plastic surgical practice is called to account by a cross-examination of the available evidence in support of many of the common treatment protocols and surgical procedures in everday use. The result is a text that makes an important contribution to some fo the contentious debates within the speciality and details the critical appraisal of new or developing techniques.